D4N2025 Presentation Showcase – Thematic Session 4B: Digital solutions for diets and nutrition - Mattinson, Rina; Karunarathna, Nilmini; Perera, Thushanthi; Ahmed, Wardah; Memon, Zahid (International Food Policy Research Institute, 2025)
This work was presented as part of the conference, Delivering for Nutrition in South Asia: Towards Impact at Scale, which took place in Kathmandu, Nepal from December 2–4, 2025. D4N2025 funders include ANH Academy, CGIAR Better Diets and Nutrition, CGIAR Scaling for Impact, Heifer International, IFPRI, UN World Food Programme, and the World Bank.